A parametric model bridging between bounded and unbounded variograms. Issue 1 (7th February 2017) - Schlather, Martin; Moreva, Olga
Abstract : A simple variogram model with two parameters is presented that includes the power variogram for fractional Brownian motion, a modified De Wijsian model, the generalized Cauchy model and the multiquadric model. One parameter controls the sample path roughness of the process. The other parameter allows for a smooth transition between bounded and unbounded variograms, that is, between stationary and intrinsically stationary processes in a Gaussian framework, or between mixing and non‐ergodic Brown–Resnick processes when modeling spatial extremes. Copyright © 2017 John Wiley & Sons, Ltd.